Impact of Blockchain Accounting on Automated Financial Reporting - Kansara, Hitarth J. (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This study investigates the transformative impact of block chain accounting on automated financial reporting, emphasizing improvements in accuracy, timeliness, operational efficiency, and return on investment (ROI). Mixed-methods research design is used which combines quantitative analysis and qualitative insights. The study reveals that organizations utilizing block chain-based systems significantly outperforms the traditional systems in terms of reporting accuracy and speed. Regression and correlation analyses further support a strong positive relationship between block chain integration and operational efficiency. The findings also underscore the importance of regulatory, organizational, and human factors in the successful adoption of block chain, with regulatory hurdles posing key challenges. The study contributes to the literature by proposing a practical framework for block chain integration and supports this empirical research that guides large-scale implementation. Block chain stands as a foundational technology with sufficient potential which redefine the standards of financial transparency, automation, and trust in modern accounting practices.